Photosensitive studies on V2O5 doped (40-x)Li2O-10Y2O3-50SiO2 glasses - Naresh, Padamati; Narasimha, Rao N.; Praveen, Chand G.; Fakruddin, Babavali Sk.; Rekha, E. (Physics and Chemistry of Solid State, 2026)
In this study, glass systems with chemical composition (40-x)Li2O–10Y2O3–50SiO2:xV2O5 were prepared using melt-quenching method. The XRD patterns of the prepared samples conform to the glassy nature. Optical absorption spectra exhibit two absorption bands at around roughly 630 nm and 1030 nm, identified as the transitions due to 2B2→2B1 and 2B2→2E transitions of [VO]2+ ions. The intensities of these identified peaks are observed to grow with a slightly red shift with the V2O5 content in the glass matrix. The direct and indirect optical band gaps, evaluated using Davis-Mott theory, decreased with increasing V2O5 concentration, while the Urbach energy obtained from the Urbach rule increased. IR spectral analysis revealed that the glass samples exhibit various structural units via., asymmetric and symmetric stretching linkages, , linkages and ; it appeared that the intensity of asymmetric linkages was observed to increase by the expense of symmetric linkages with a gradual increase in the content of V2O5. The optical absorption spectra of the investigated glasses suggest the coexistence of V4+ and V5+ ionic species. The observed evolution of the characteristic vanadyl absorption bands with increasing V2O5 concentration indicates a possible shift in the V4+/V5+ equilibrium within the glass network.